Structural elucidation of metolachlor photoproducts by liquid chromatography/high‐resolution tandem mass spectrometry. (28th October 2015) - Nicol, Édith; Genty, Christophe; Bouchonnet, Stéphane; Bourcier, Sophie
Abstract : Rationale: Metolachlor is one of the most intensively used chloroacetanilide herbicides in agriculture. It has been detected in water; consequently, under UV‐visible irradiation, it can be transformed in degradation products (TPs). The structures of TPs were elucidated by liquid chromatography/high‐resolution tandem mass spectrometry (LC/HR‐MS/MS). The potential toxicities of these TPs were estimated by in silico tests. Methods: Aqueous solutions of metolachlor were irradiated in a self‐made reactor equipped with a mercury vapor lamp. Analyses were carried out using high‐performance liquid chromatography coupled to quadrupole time‐of‐flight (QTOF) mass spectrometer. High‐resolution m / z measurements, MS/MS and isotopic labeling experiments allowed structural elucidation of metolachlor TPs. Their toxicities were estimated in silico, using the T.E.S.T. program. Results: Ten major metolachlor photoproducts were characterized by LC/MS/MS after irradiation of metolachlor in aqueous solution. Elucidation of their chemical structures was identified using high‐resolution measurements and MS/MS experiments. They resulted from the combination of dehalogenation, hydroxylation and cyclisation processes. The potential oral rat lethal dose (LD50) was assessed with QSAR tests for metolachlor and each photoproduct. Results indicate that most of the TPs are much more toxic than metolachlor. Conclusions: UV–vis irradiation of metolachlor in aqueous solution leads to the formation of ten photoproducts. QSAR estimations show that the location of added hydroxyl group(s) is of key relevance as regards to biological activity and that routine water analysis should take into account the TPs are more toxic than the parent molecule. Copyright © 2015 John Wiley & Sons, Ltd.